Lagrangian Decomposition of the Atlantic Ocean Heat Transport at 26.5°N - Tooth, OJ; Foukal, NP; Johns, WE; Johnson, HL; Wilson, C (Wiley Open Access, 2024)
The Atlantic Meridional Overturning Circulation (AMOC) plays a critical role in the global climate system through the redistribution of heat, freshwater and carbon. At 26.5°N, the meridional heat transport has traditionally been partitioned geometrically into vertical and horizontal circulation cells; however, attributing these components to the AMOC and Subtropical Gyre (STG) flow structures remains widely debated. Using water parcel trajectories evaluated within an eddy‐rich ocean hindcast, we present the first Lagrangian decomposition of the meridional heat transport at 26.5°N. We find that water parcels recirculating within the STG account for 37% (0.36 PW) of the total heat transport across 26.5°N, more than twice that of the classical horizontal gyre component (15%). Our findings indicate that STG heat transport cannot be meaningfully distinguished from that of the basin‐scale overturning since water parcels cooled within the gyre subsequently feed the northward, subsurface limb of the AMOC.